2019
DOI: 10.1021/acs.jpcc.9b09918
|View full text |Cite
|
Sign up to set email alerts
|

Damping of Cu-Associated Photoluminescence and Formation of Induced Absorption in Heavily Cu-Doped CdSe Quantum Dots

Abstract: We studied photoluminescence (PL) properties and nonlinear absorption characteristics of heavily Cu-doped CdSe colloidal quantum dots (QDs) under nanosecond laser pulse excitation. A strong dependence of basic exciton transition behavior and Cu dopant-associated PL on the concentration of copper ions and pump intensities was revealed for the first time. The saturation of the copper-associated PL signal was found to happen much faster than the saturation of nonlinear absorption. The induced absorption and satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…instead of spreading the phenomenon of focussing is observed. Also, if bt * { 1 this could happen at intermediate time scales for total MSD since then the displacement can be determined by free particles as it is shown from a comparison of eqn (19) and (20). Surely the exciton switches between the free and the trapped states, and MSD describes different sets of particles at different times.…”
Section: Power-law Casementioning
confidence: 99%
See 1 more Smart Citation
“…instead of spreading the phenomenon of focussing is observed. Also, if bt * { 1 this could happen at intermediate time scales for total MSD since then the displacement can be determined by free particles as it is shown from a comparison of eqn (19) and (20). Surely the exciton switches between the free and the trapped states, and MSD describes different sets of particles at different times.…”
Section: Power-law Casementioning
confidence: 99%
“…They are formed when light interacts with a wide variety of systems. This includes inorganic and organic molecular semiconductors, [1][2][3] photosynthetic complexes, 4,5 polymers, [6][7][8] molecular aggregates, [9][10][11] semiconductor quantum wells and quantum wires, [12][13][14][15] colloidal quantum dots and nanoplatelets, [16][17][18][19][20][21][22][23][24][25] transition metal dichalcogenides, [26][27][28][29][30] and perovskites. [31][32][33][34][35][36][37] The dynamical properties of these systems are crucial for the advancement of optoelectronic applications including novel lasers, 16 photodetectors, 38 light-emitting diodes [39][40][41] and solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that silica coating stabilizes NTPs, but a systematic investigation of the effect of such shelling on ϕ PL is yet to be performed . On a different note, only a few reports exist on transition-metal doping in NTPs, , but it is a popular strategy to enhance ϕ PL , excited-state lifetime and transportation time, as well as charge collection efficiency, which make them potential candidates for application in luminescent solar cells (LSCs) and light-emitting diodes (LEDs). The key process, which is responsible for all these observations is the disruption of overlap between electron and hole wavefunctions, leading to a breakdown of electron–hole correlation, once the hole is captured by Ag in doped NCs . After hole capture by Ag, the hole wavefunction is localized only to the doped state, but the electron wavefunction is delocalized thoughtout the conduction band (CB) (Schemes B and S1).…”
Section: Introductionmentioning
confidence: 99%
“…17 Modern techniques of precise colloidal synthesis allow control of the shape, 18 size 19 and crystal structure of the nanocrystals. 20 Among these, there is a growing popularity of colloidal QDs and NPLs of CdSe with atomically defined thickness 5,21,22 and various shapes such as pure QDs and NPLs (core) as well as composite core-shell QDs and NPLs or core-crown NPLs. The composites are made of two different semiconductor materials, for instance, CdSe and CdS.…”
Section: Introductionmentioning
confidence: 99%